Applied Data Science for Analyzing the Mediating Role of Digital Transformation Influencing Banking Business Efficiency in Vietnam - Huy, Nguyen Quoc; Tam, Phan Thanh (Bright Publisher, 2025)
In the context of accelerated digitalization and growing competitive pressures, commercial banks in emerging economies urgently need to enhance internal capabilities to drive innovation and performance. This study investigates how key organizational factors, including employee engagement, leadership style, corporate culture, financial capacity, and management capacity, influence creative innovation and digital transformation and how these, in turn, impact business efficiency in Vietnamese commercial banks. Grounded in the Resource-Based View and Dynamic Capabilities Theory, the research develops and empirically tests a comprehensive structural model using data collected from 942 banking professionals across 30 commercial banks in Vietnam. A mixed-methods approach was employed, combining expert interviews with a large-scale survey. Structural Equation Modeling (SEM) and bootstrapped mediation analysis were used to test 17 hypotheses. The results reveal that all five internal factors positively influence Creative Innovation (CI) and Digital Transformation (DT). Notably, employee engagement and management capacity emerged as the strongest drivers. Creative innovation exerts the most significant direct effect on business efficiency, while digital transformation plays a complementary but weaker mediating role. The findings validate a multi-layered framework linking organizational dynamics to performance, offering novel insights into how banks can align internal resources with strategic goals. This study contributes to the literature by positioning creative innovation and digital transformation as mediators between organizational capabilities and business outcomes. It also provides actionable recommendations for bank executives seeking to enhance operational efficiency through people-centered, innovation-led strategies tailored to the context of emerging markets. Finally, policymakers and bank leaders should implement digital Key Performance Indicators (KPIs), foster employee-led innovation, invest in managerial training, and align human resource incentives with transformation goals to enhance efficiency and resilience in Vietnam's banking sector.